“I Love It When You Play that Holy Ghost Chord”: Sounding Sacramentality in the Black Gospel Tradition - Braxton D. Shelley (Religions, 2020)
This essay argues that the distinctive aesthetic practices of many African American Christian congregations, indexed by the phrase “the Black gospel tradition”, are shaped by a sacramentality of sound. I contend that the role music routinely plays in the experience of the holy uncovers sanctity in the sound itself, enabling it to function as a medium of interworldly exchange. As divine power takes an audible form, the faith that “comes by hearing” is confirmed by religious feeling—both individual and collective. This sacramentality of sound is buttressed by beliefs about the enduring efficacy of divine speech, convictions that motivate the intensive character of gospel’s songs, sermons, and shouts. The essay begins with a worship service from Chicago, Illinois’ Greater Harvest Missionary Baptist Church, an occasion in which the musical accompaniment for holy dancing brought sound’s sacramental function into particularly clear relief. In the essay’s second section, I turn to the live recording of Richard Smallwood’s “Hebrews 11”, a recording that accents the creative power of both divine speech and faithful utterances, showing how reverence for “the word of God” inspires the veneration of musical sound. In the article’s final move, I show how both of the aforementioned performances articulate a sacramental theology of sound—the conviction that sound’s invisible force brings spiritual power to bear on the material world.